Single-Cell Analysis of Neuroinflammatory Responses Following Intracranial Injection of G-Deleted Rabies Viruses - Huang, Kee Wui; Sabatini, Bernardo L. (Frontiers in Cellular Neuroscience, 2020)
Viral vectors are essential tools for the study of neural circuits, with glycoprotein-deleted rabies viruses being widely used for monosynaptic retrograde tracing to map connectivity between specific cell types in the nervous system. However, the use of rabies virus is limited by the cytotoxicity and the inflammatory responses these viruses trigger. While components of the rabies virus genome contribute to its cytotoxic effects, the function of other neuronal and non-neuronal cells within the vicinity of the infected host neurons in either effecting or mitigating virally-induced tissue damage are still being elucidated. Here we analyzed 60,212 single-cell RNA profiles to assess both global and cell type-specific transcriptional responses in the mouse dorsal raphe nucleus following intracranial injection of glycoprotein-deleted rabies viruses and axonal infection of dorsal raphe serotonergic neurons. Gene pathway analyses revealed a down-regulation of genes involved in metabolic processes and neurotransmission following infection. We also identified several transcriptionally diverse leukocyte populations that infiltrate the brain and are distinct from resident immune cells. Cell type-specific patterns of cytokine expression showed that antiviral responses were likely orchestrated by Type I and Type II interferon signaling from microglia and infiltrating CD4+ T cells, respectively. Additionally, we uncovered transcriptionally distinct states of microglia along an activation trajectory that may serve different functions, which range from surveillance to antigen presentation and cytokine secretion. Intercellular interactions inferred from transcriptional data suggest that CD4+ T cells facilitate microglial state transitions during the inflammatory response. Our study uncovers the heterogeneity of immune cells mediating neuroinflammatory responses, and provides a critical evaluation of the compatibility between rabies-mediated connectivity mapping and single-cell transcriptional profiling. These findings provide additional insights into the distinct contributions of various cell types in mediating different facets of antiviral responses in the brain, and will facilitate the design of strategies to circumvent immune responses to improve the efficacy of viral gene delivery.